Application of the Milan System for Reporting Salivary Gland Cytopathology to cystic salivary gland lesions. Issue 3 (1st October 2020) - Maleki, Zahra; Allison, Derek B.; Butcher, Monica; Kawamoto, Satomi; Eisele, David W.; Pantanowitz, Liron
Abstract : Background: Cystic salivary gland lesions present diagnostic challenges on fine‐needle aspiration (FNA) specimens that are related to sampling limitations and a broad differential diagnosis. This study evaluated the benefit of applying the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) to a series of cystic salivary gland lesions. Methods: The pathology archives at the Johns Hopkins Hospital were searched to identify cystic salivary gland FNA specimens over a 19‐year period (2000‐2018). Patient demographics, cytomorphologic features, and clinical and surgical follow‐up were recorded. The MSRSGC was applied to the cases. The risk of malignancy (ROM) and the risk of neoplasia (RON) were calculated for each category. Results: One hundred seventy‐eight cases were identified (96 males and 82 females) with a mean age of 53 years (range, 4‐90 years). After the MSRSGC was applied, there were 52 nondiagnostic cases (29.2%), 80 nonneoplastic cases (44.9%), 35 cases of atypia of undetermined significance (AUS; 19.7%), 3 benign neoplasms (1.7%), 3 salivary gland neoplasms of uncertain malignant potential (SUMP; 1.7%), 4 cases suspicious for malignancy (SFM; 2.2%), and 1 malignant case (0.6%). One hundred fifty‐six of the 178 patients (87.6%) had follow‐up data available. The RON and ROM values for cases with surgical follow‐up were 33.3% (3 of 9) and 22.2% (2 of 9) for the nondiagnostic category, 42.9% (9 of 21) and 19% (4 of 21) for the nonneoplastic category, 76.5% (13 of 17) and 29.4% (5 of 17) for the AUS category, 100.0% (2 of 2) and 50.0% (1 of 2) for the SUMP category, and 100% (2 of 2) and 100% (2 of 2) for the SFM category, respectively. Conclusions: Applying the MSRSGC to cystic salivary gland lesions improves patient management by preventing unnecessary surgery for nonneoplastic conditions. The ROM was highest in the SFM category (100%), which was followed by the SUMP, AUS, nondiagnostic, and nonneoplastic categories. Less than adequate specimens may increase the diagnosis of AUS. Abstract : The application of the Milan System for Reporting Salivary Gland Cytopathology to cystic salivary gland lesions provides valuable information for guiding clinical management and may prevent unnecessary surgery in a considerable number of cases. The risk of neoplasia and the risk of malignancy are 6.25% and 4.2% for the nondiagnostic category, 12.3% and 5.4% for the nonneoplastic category, 52% and 20% for the atypia of uncertain significance category, 100% and 0% for the benign neoplasm category, 100.0% and 50.0% for the salivary gland neoplasm of uncertain malignant potential category, and 66.7% and 66.7% for the suspicious for malignancy category, respectively.